Hippocampal neural activity reflects the economy of choices during goal-directed navigation - Tryon, Valerie L. (Hippocampus, 2017)
Distinguishing spatial contexts is likely essential for the well-known role of the hippocampus in episodic memory. We studied whether types of hippocampal neural organization thought to underlie context discrimination is impacted by learned economic considerations of choice behavior. Hippocampal place cells and theta activity were recorded as rats performed a maze-based probability discounting task that involved choosing between a small certain reward or a large probabilistic reward. Different spatial distributions of place fields were observed in response to changes in probability, the outcome of the rats’ choice, and whether or not rats were free to make that choice. The degree to which the reward location was represented by place cells scaled with the expected probability of rewards. Theta power increased around the goal location also in proportion to the expected probability of signaled rewards. Further, theta power dynamically varied as specific econometric information was obtained ‘on the fly’ during task performance. Such an economic perspective of memory processing by hippocampal place cells expands our view of the nature of context memories retrieved by hippocampus during adaptive navigation.